PEREMPUAN DAN KEKUASAAN POLITIK: EVALUASI STUDI-STUDI GENDER BERBASIS BIBLIOMETRIK DI ASIA TENGGARA 2004-2024 - Yuniar Galuh Larasati; Larasati, Yuniar Galuh; Fernando, Henky (Center of Gender Studies and Child of State Islamic Institute of Metro, 2025)
This study aims to explain and analyze studies that discuss women's issues in political power in Southeast Asia, based on Scopus database publication documents in the last two decades 2004-2024. In addition to using bibliometric-based analysis methods, this study also uses VOSviewers application-based software in explaining and analyzing trends, patterns, and developments of studies that have been conducted based on Scopus database publication documents in the last two decades 2004-2024. The findings in this study show that the trends, patterns, and development of studies that discuss women's issues in political power have not been conducted comprehensively. The results of this exploration and evaluation are the basis for this study to recommend the importance of future studies that focus on analyzing the adaptation and transformation of the contemporary political system in adopting the welfare of vulnerable groups. Thus, knowledge about the conception and praxis of a political system that accommodates vulnerable groups can be comprehensively explored and evaluated, so that women's problems in contemporary political issues can be addressed effectively and efficiently based on the findings of future studies.